BRYOPHYTE DIVERSITY ACROSS A DIFFERENT POST-ERUPTION SUCCESSIONAL GRADIENT IN MOUNT PAPANDAYAN, WEST JAVA - Mufidah, Nada
Bryophytes play an important part in biodiversity, particularly in tropical rainforests, in water retention, and as habitat and food for small animals. Although bryophytes are adapted to grow in various habitats, only limited information was available regarding important factors that determine bryophyte diversity and cover. The massive volcanic eruption on Mount Papandayan in 2002 caused extreme changes in the landscape. Those changes were followed by a succession characterized by colonization by both plants of higher orders and bryophytes. Therefore, this study was conducted to assess bryophyte diversity 18 years post-eruption and the factors driving bryophyte colonization in Mount Papandayan. A total of 141 plots of 20 cm x 20 cm were established at three sites based on the intensity of disturbance, i.e., Hutan Mati (HM) as high disturbance intensity site, Pondok Saladah (PS) as a moderately disturbed site, and Hutan Cisupabeureum (HC) as the least disturbed site. Bryophyte diversities, including species richness, Shannon-Wiener Index, and Simpson’s Index, were assessed. Bryophyte cover was recorded in three substrates (soil, tree base, and tree bark) and classified according to its taxonomy and life forms. Effects of land productivity (measured by normalized difference vegetation index), distance from the crater (source of disturbance), average relative humidity, and elevation to bryophyte cover were investigated using linear mixed models (LMM). We recorded 56 species belonging to 18 families and six types of life forms. In the highly and moderately disturbed sites, mosses such as Barbula sp. (IV = 126.9) and Dicranodontium nitidum (IV = 90.43) dominated, whereas, in the less disturbed areas, fan-like mosses such as Homaliodendron flabellatum (IV = 35.19) were abundant. Bryophyte diversity and cover had decreased in highly disturbed sites, which was attributable to the loss of microhabitats such as the bark of trees and shaded patches. The result also suggests that bryophyte cover in the area disturbed by the eruption is driven by the combination of distance from the crater, land productivity, and average relative humidity, where the distance from the crater positively drives bryophyte cover. This study suggests that after 18 years, the area near the crater was still in its initial stage of succession based on bryophyte colonization.